ISOLATED PROTEIN FROM CASTOR BEAN, PEANUT, SOY BEAN AND SAFFLOWER MEALS - B.Tavasolian; S.Nikpour; B.Makanvand (Tehran University of Medical Sciences, 1981)
Castor bean, peanut, Soy bean and safflower protein isolates were prepared. The amino acid content of each of the protein isolates was analysed and the essential amino acid contents were compared with the FAO human requirements. The results indicated that castor bean has the highest oil and the protein content of defatted meal. Safflower 3148 (Marand, Iran) has the highest amount of essential amino acids. Peanut (Gilan Iran) has the lowest content of essential amino acids, however, in comparison to human requirement 100 gram protein of this peanut still have enough amino acid for one man's day. The ash total protein and total oil of the mentioned seeds were also determined.